2015
DOI: 10.1063/1.4907972
|View full text |Cite
|
Sign up to set email alerts
|

Observation of two polytypes of MoS2 ultrathin layers studied by second harmonic generation microscopy and photoluminescence

Abstract: Second harmonic generation (SHG) of a high intensity was found in MoS2 flakes of different thicknesses exfoliated on a silicon substrate. Reduction of the SHG intensity was observed only for a small portion of flakes, for both very thin and quite thick ones. This was attributed to the presence of polytypism, i.e., of 3R non-centrosymmetric and 2H centrosymmetric polytypes, in a source bulk crystal grown by the chemical vapor transport technique. The presence of two polytypes in the sample was confirmed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 27 publications
1
22
0
1
Order By: Relevance
“…Microc rystallites with the most pronounced features at the edges were chosen for further investigation. In the pre vious study, using the SHG anisotropy method [22], we showed that each exfoliated microcrystallite is a single crystal.…”
Section: Edge Effects In Second Harmonic Generation In Nanoscale Layersmentioning
confidence: 96%
“…Microc rystallites with the most pronounced features at the edges were chosen for further investigation. In the pre vious study, using the SHG anisotropy method [22], we showed that each exfoliated microcrystallite is a single crystal.…”
Section: Edge Effects In Second Harmonic Generation In Nanoscale Layersmentioning
confidence: 96%
“…Следующим шагом являлось нанесение монослойных кристаллитов MoS 2 на подложку методом механической эксфолиации [15,16]. Поиск и выбор кристаллитов для изготовления фотодетектора осуществлялись с помощью комплексной методики оптического контроля характеристик дихалькогенидов.…”
Section: экспериментальные образцы и методикиunclassified
“…this confirms the presence of centrosymmetric 2H and non-centrosymmetric 3R polytypes in a source bulk sample, which is made into the flakes. SHG intensity dependences on the Azimuthal position and on the flake thickness and the PL spectra are used to analyze this property [42] . This kind of polytypism in TMDC Materials will be very helpful in device fabrication techniques.…”
Section: Optical Propertiesmentioning
confidence: 99%